The Effect of Safety Management Practices Through Safety Knowledge Towards Safety Performance on Workers of Pt. Masmindo Dwi Area - Ummu Kamilah; Syamsiar S. Russeng; Masyitha Muis; Yahya Thamrin; Masni; Fridawati Rivai; Rizky Maharja (Indian Journal of Forensic Medicine & Toxicology, 2021)
Accidents in a workplace are caused by many human errors in form of unsafe behavior. One of the efforts toprevent work accidents is to improve safety performance in form of participation and obedience. Improvementof safety performance in workplace is affected by management and individual factors. Management factoris mainly associated with safety management practices while individual factor is associated with individualcharacteristics and occupational health and safety knowledge and training. This study aims to analyze theeffect of individual factors and safety management practices on safety performance among workers at PT.Masmindo Dwi area. This research is a quantitative research using analytic observational and cross sectionaldesign which was conducted in November-December 2020. Interviews were conducted on 72 workers outof 289 workers. The methods used in assessing safety management practices, individual factors and safetybehavior are questionnaires, observation and interviews. The results showed that there is a direct (p=0,024)and indirect effect (p=0,001) of safety management practices on safety performance with safety knowledgeas a mediating variable. Writer highly advise that in improving safety performance, the management haveto be consistent, show commitments to safety rules and procedures that have been made, improve safetytraining programs, and increase the quantity and quality of training programs.